2012
DOI: 10.4088/jcp.12l08013
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Major Malformations in Infants Following Exposure to Duloxetine During Pregnancy

Abstract: To the Editor: There are no published prospective, comparative studies examining the safety of duloxetine in pregnancy, and, to date, there are only 2 case reports describing its use in pregnancy:(1) a 29-year-old woman was treated with duloxetine for depression during the second half of pregnancy and gave birth to a full-term healthy infant, 1 and (2) an infant was observed after birth with signs of possible poor neonatal adaptation, following exposure in utero to duloxetine in late pregnancy. 2 Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 2 publications
4
11
0
Order By: Relevance
“…In the toxicological field, a number of mild or moderate effects have been described including dry mouth, nausea, insomnia, somnolence, dizziness, headache, constipation, and sexual dysfunction. 15) More severe affections such as microscopic or lymphocytic colitis, pseudolymphoma, hyponatremia, various types of hepatic injury, and major malformations 16) have also been sporadically registered. Regarding preclinical and clinical security, genotoxic studies constitute a highly relevant approach because these studies can demonstrate the capacity of the compound to induce genic and chromosome alterations, which can be the basis of future disease development, such as various chronic degenerative illnesses and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the toxicological field, a number of mild or moderate effects have been described including dry mouth, nausea, insomnia, somnolence, dizziness, headache, constipation, and sexual dysfunction. 15) More severe affections such as microscopic or lymphocytic colitis, pseudolymphoma, hyponatremia, various types of hepatic injury, and major malformations 16) have also been sporadically registered. Regarding preclinical and clinical security, genotoxic studies constitute a highly relevant approach because these studies can demonstrate the capacity of the compound to induce genic and chromosome alterations, which can be the basis of future disease development, such as various chronic degenerative illnesses and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by Einarson et al . () on the use of DUL in 256 pregnant women; among these, the majority ( n = 206) took DUL in the first trimester, two during the second and third trimesters, and the others throughout the pregnancy. The rate of MMs (1.8% consisting in clubfoot, kidney agenesis, and hydronephrosis) was within the baseline rate in the general population.…”
Section: Duloxetine In Pregnancymentioning
confidence: 99%
“…In a multicenter, prospective, observational study, Einarson et al 16 followed 208 women who had directly or through their health care providers inquired about the safety of duloxetine during pregnancy. Of these, 206 women (99.0%) took duloxetine before conception and during early pregnancy, 51 (24.5%) used it all through pregnancy, and 2 took it only during the second or third trimesters.…”
Section: Clinical Pointsmentioning
confidence: 99%
“…Other pregnancy outcomes were not reported in this study. 16 Hoog et al 17 reported on 400 cases of duloxetine exposure during pregnancy for which pregnancy outcome information was available. These cases were identified from the Eli Lilly Safety System database.…”
Section: Clinical Pointsmentioning
confidence: 99%